Action Research for Development of Enhancing Community Vaccines Model in The Situation of COVID-19 Outbreak - Junprasert, Thasuk; Wongsawat, Suda; Chusanachote, Pongpol (Journal of Behavioral Science for Development, 2022)
This study focuses on developing community vaccines. Action Research was applied. Pak Phli District, Nakhon Nayok Province, and Mae Wang District, Chiang Mai province were selected as a model community that participants in the community participated in this study. The study is divided into 2 phases: Phase 1: Workshop research to create and develop a form of vaccine for the mind in the community. Phase 2: synthesizes the form and creates a guideline to create a vaccine for the mind in the community. Qualitative method and Content Analysis were used. The results showed that the model of building and developing of vaccine of mind consist of 5 steps which are 1) searching for community capital and community potential 2) building a multi-level network 3) defining a mind vaccine target by using community bond and potential based on 4 Build 2 Use 4) implementation and refection and 5) community jointly monitoring. The outcomes for mental health change after participating in the model as the following: 1) having the ability to manage emotions, 2) feeling safe and trusting, 3) living with goals and hope. From the results, the model can be extended to other areas to encourage communities to cooperate in the face of various crises, to be able to prevent, solve problems, and quickly recover to normal conditions. However, some adjustment for different context might be needed. Lasty, it is important to build multi-network levels’ co-operation to promote a successful co-operation and drive further policy.